EDUCATION OF EUROPEAN FLUENCY SPECIALISTS The European Clinical Specialization on Fluency Disorders (ECSF) - LEAHY, MARGARET M (My University, 2011)
The European Clinical Specialization on Fluency Disorders (ECSF) project consists of one-year post-qualification fluency specialization training and a harmonized graduate fluency program. It was developed by eight European universities/colleges to provide the means whereby graduates would meet comparable standards of competence to practice in the field of fluency disorders. In this paper we describe criteria that guided the consortium in their decision making process to create an optimal learning environment for participants. A review of the first completed course cycle, with 23 international participants, is discussed.
PUBLISHED
Keywords: Education; European Clinical Specialization on Fluency Disorders (ECSF)